New Actors and Democratic Governance in a Rising Africa - Ahere, John Rabuogi (Frontiers in Political Science, 2021)
This paper broadly examines the continued nuancing of the practice of democracy in Africa with a focus on how Africa’s democratic governance is increasingly getting influenced by new actors in the international system, who are driving the formation of a new world order that challenges the current unipolar liberal global order. The paper traces the origins and rationale of the democratization project in Africa and uses this as a basis to delve into some issues around which many African countries have increasingly been engaging with new actors. These broad aspects include: Africa’s international relations, peace and security; civil liberties as well as investments and trade. This paper contends that some states in Africa are charting middle grounds that increasingly, specifically align with their national/elite interests, and broadly, is in tune with the consolidating discourse on Africa Rising.